What is the relationship between chronic alcohol consumption and liver function markers in adult ? : A Systematic Review - Nevan Bayu Sunggoro (International Medical Journal Corp. Ltd, 2025)
Introduction: Chronic alcohol consumption is a leading cause of preventable liver disease globally. This systematic review synthesizes and evaluates current evidence on the significant relationship between chronic alcohol consumption and liver function markers in adults. Methods: Following PRISMA guidelines , a systematic search was conducted across PubMed, Semantic Scholar, Springer, and Google Scholar. Inclusion criteria targeted observational studies, systematic reviews, and meta-analyses that quantified alcohol intake and measured liver function markers (e.g., ALT, AST, GGT) in adults without pre-existing non-alcoholic liver disease. After screening, 24 studies were selected for data extraction and synthesis. Results: The findings demonstrate a significant dose-dependent relationship, where increasing alcohol consumption corresponds with elevated liver enzymes, particularly AST, ALT, and GGT. GGT was identified as the most sensitive marker for alcohol-related liver stress. An AST/ALT ratio greater than one was a strong and significant indicator of alcohol-specific liver injury. Liver damage was cumulative, with longer duration of consumption leading to progressively worse outcomes. Binge drinking emerged as a significant risk factor for hepatic steatosis, independent of average weekly intake. Significant population variability was observed; women are more susceptible at lower doses , and a potential protective effect of light drinking on fatty liver was noted uniquely in Japanese cohorts. Conclusion: Chronic alcohol consumption is conclusively linked to impaired liver function in a dose- and duration-dependent manner. Susceptibility is significantly modulated by sex, genetics, ethnicity, and comorbidities like obesity. While methodological reliance on self-reported intake is a common limitation , the evidence strongly supports using GGT for early screening and the AST/ALT ratio for diagnostics.